Free Nutritional Meal Program: Ensuring Rights Are Fulfilled and Obligations Are Implemented on Target - Anggraini Oktavia Ramadhani; Desi Alia Putri Astuti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The Free Nutritious Meal Program (MBG) is a straSStegic government initiative aimed at addressing nutritional problems and improving the quality of human resources, while also serving as a concrete manifestation of the state's obligation to fulfill citizens’ fundamental right to adequate food. This study aims to critically analyze the challenges in implementing the program and examine the legal accountability mechanisms involved. The method used is a literature study by collecting and analyzing data from relevant books and scientific journals. The discussion shows that the program’s juridical foundation is firmly rooted in the 1945 Constitution and Pancasila as an embodiment of social justice. However, field implementation faces significant obstacles, including inaccuracies in beneficiary data prone to human error, the complexity of logistical distribution, and issues regarding food quality that is sometimes unfit for consumption. Failures in these aspects risk violating children’s constitutional rights and causing budget inefficiency. Therefore, improvement strategies are needed, including digitalization of reporting data, clear Standard Operating Procedures (SOPs) for logistics, and multilayered supervision involving public participation to ensure that the program runs accurately, transparently, and accountably.